2021
DOI: 10.1128/msphere.00476-21
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of Human Leukocyte Antigen on the Human Gut Microbiota

Abstract: The microorganisms that live in the digestive tracts of humans, known as the gut microbiota, are essential for hosts’ survival, as they support crucial functions. For example, they support the host in facilitating the uptake of nutrients and give colonization resistance against pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 70 publications
(92 reference statements)
0
13
0
Order By: Relevance
“…Meanwhile, a recent study quantifying Il-10 deficiency in BDC2.5 + NOD mice increased susceptibility to islet autoimmunity through modulating neutrophil hemostasis, an effect accompanied by altered intestinal immunity and gut microbiome profile. [29] the influence of HLA alleles on human gut microbiota reported that individuals with similar HLA genes have similar microbiota profiles [42]. A correlation between variants located in the HLA region and gut microbiome composition was also found in a mGWAS study [47].…”
Section: Mhc Polymorphismsmentioning
confidence: 80%
See 3 more Smart Citations
“…Meanwhile, a recent study quantifying Il-10 deficiency in BDC2.5 + NOD mice increased susceptibility to islet autoimmunity through modulating neutrophil hemostasis, an effect accompanied by altered intestinal immunity and gut microbiome profile. [29] the influence of HLA alleles on human gut microbiota reported that individuals with similar HLA genes have similar microbiota profiles [42]. A correlation between variants located in the HLA region and gut microbiome composition was also found in a mGWAS study [47].…”
Section: Mhc Polymorphismsmentioning
confidence: 80%
“…Subsequently, an accumulating body of research on transgenic and congenic mice indicated that MHC genetics contributes to shaping the gut microbiome, influencing the genesis and development of diseases [ 32 , 44 , 46 ]. Meanwhile, a recent study quantifying the influence of HLA alleles on human gut microbiota reported that individuals with similar HLA genes have similar microbiota profiles [ 42 ]. A correlation between variants located in the HLA region and gut microbiome composition was also found in a mGWAS study [ 47 ].…”
Section: Mhc Polymorphismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, regional differences in commensal microbiota composition may be considered a distinct category of environmental-driven endotype. However, mutual regulation and feedbacks make it difficult to draw a clear line between genetics- and environment-driven endotypes as HLA differences have been reported to influence the gut microbiome ( 193 ). A recent report indicated that individuals carrying at-risk HLA haplotypes seem to have a distinct core microbiome and beta diversity compared to the general population ( 194 ).…”
Section: Discussionmentioning
confidence: 99%